MORPHOLOGY AND SIGNIFICATION OF GELE EPHEMERAL ART - Акінде, Тойін Еммануель (Art and Design, 2023)
The purpose of this study is to identify selected contemporary gele morphologies, establishing their signification(s) in line with Yoruba world views. Gele is an ephemeral artistic piece with representation in anything and everything that constitute feminine head covering, hitherto adorned by the Yoruba on casual and non-casual costume. The art, though with apparent scholastic dearth; its contemporaneous growth and intoxicating morphologies in modern fashion, has made this attempt on its signification germane and expedient. Combines field investigative approach with bibliographical method. Thirteen (13) gele practitioners were consulted, there social media handles verified and consent sought on post photographs usage. The photographic pieces were subsequently subjected to literary analyses from the Yoruba view points. Morphologically, revealed six categorizations of manual gele; establishing fragility, truth, authority and treasure significations for zoomorphic (butterfly), anthropo-artificial (hand-fan) and flora (leave and rose) subjects respectively. Attests gele feminine domiciliation, practice uni-sexuality and technique fundamentality in manual or auto. It further attests hobbyists benevolence and professional capitalism; recognising gele as a major player in Yoruba ephemeral art, worthy of promotion in consonant with sustainable development goals. This study is a clarion call on artists and patrons alike on the need to be alive to gele significations as in its morphologies. Consequently, recommends concrete postulation of gele art to fossilized art by sculptors and ceramicists alike.